Interdisciplinary evidence-based tumor board simulation training in surgical medical education - Altmayer, Nora Corinna; Khajeh, Elias; Fellhofer-Hofer, Johanna; Lintner, Anna; Fink, Matthias A.; Schwab, Constantin; Halama, Niels; Nickel, Felix; Mehrabi, Arianeb; Klupp, Fee (Langenbeck's archives of surgery, 2025)
Evidence-based medicine (EBM), precision medicine and interdisciplinarity are becoming increasingly important in medical education. The purposeful connection between EBM and interdisciplinary work is given in the context of a tumor board, since therapy decisions are discussed here in an interdisciplinary team based on current evidence-based guidelines. To date, there has been little focus on either topic. Therefore, we aimed to assess the existing knowledge and offered a practical exercise in terms of a tumor board simulation training for medical students during their surgical study semester.
Gesehen am 28.01.2026